Aviation Conflict Mediation Model Based on Dynamic Particle Swarm Algorithm - Tu, Yonglin; Xu, Haoli; Yang, Xing; Lu, Yun; Mu, Hua; Wang, Yangyang; Zhang, Chi; Liu, Xinyue; Gao, Xinglong; Zhang, Zhaoxin (2023 3rd International Signal Processing, Communications and Engineering Management Conference (ISPCEM), 2023)
With the increasing demand of air transportation, various types of aircrafts and transport planes often need to be deployed at the same time and space, which leads to the contradiction between the surge of air demand and the limited airspace resources. This paper relies on the improved dynamic particle optimization algorithm to establish a relief model for regulating the contradiction of airspace demand of various aircrafts, and experimentally verifies the feasibility and advantages of the model, and simulates the mediation of hundreds of conflicting airspace demands. The model can achieve global optimization between small fitness differences, and the optimization of the scheme can be achieved with a very small number of iterations. It provides a referable solution for problems with multiple local optimal solutions and complex nonlinear problems.